Assessing pandemic preparedness, response, and lessons learned from the COVID-19 pandemic in four south American countries: agenda for the future - Ramírez Varela, Andrea; Touchton, Michael; Miranda, J. Jaime; Grueso, Juliana Mejía; Laajaj, Rachid; Carrasquilla, Gabriel; Florez, Martha Vives; Gaviria, Ana María Vesga; Hoyos, Ana María Ortiz; Duarte, Esteban Orlando Vanegas; Morales, Alejandra Velásquez; Velasco, Nubia; et al. (Frontiers in Public Health, 2023)
Introduction The COVID-19 pandemic emerged in a context that lacked adequate prevention, preparedness, and response (PPR) activities, and global, regional, and national leadership. South American countries were among world’s hardest hit by the pandemic, accounting for 10.1% of total cases and 20.1% of global deaths. Methods This study explores how pandemic PPR were affected by political, socioeconomic, and health system contexts as well as how PPR may have shaped pandemic outcomes in Argentina, Brazil, Colombia, and Peru. We then identify lessons learned and advance an agenda for improving PPR capacity at regional and national levels. We do this through a mixed-methods sequential explanatory study in four South American countries based on structured interviews and focus groups with elite policy makers. Results The results of our study demonstrate that structural and contextual barriers limited PPR activities at political, social, and economic levels in each country, as well as through the structure of the health care system. Respondents believe that top-level government officials had insufficient political will for prioritizing pandemic PPR and post-COVID-19 recovery programs within their countries’ health agendas. Discussion We recommend a regional COVID-19 task force, post-pandemic recovery, social and economic protection for vulnerable groups, improved primary health care and surveillance systems, risk communication strategies, and community engagement to place pandemic PPR on Argentina, Brazil, Colombia, and Peru and other South American countries’ national public health agendas.